Manajemen Berbasis Sekolah dalam Meningkatkan Mutu Pendidikan di Smp Negeri 02 Purworejo - Hodin (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2020)
This research is based on the importance of school-based management in improving the quality of education. In this regard, this study aims to determine School-Based Management in Improving the Quality of Education at SMP Negeri 02 Purworejo. This research is a qualitative research. Data collection used interviews, observation, and documentation, and the validity of the data used triangulation, and data analysis techniques included data collection, data reduction, data presentation, and drawing conclusions. This research resulted in four conclusions: (1) School autonomy in improving the quality of education at SMP Negeri 2 Purworejo with School Based Management (SBM) has been running according to the provisions of the applicable regulations. (2) School participation in improving the quality of education, namely that schools always involve school committees in planning and establishing policies, school committees also play an active role in assisting the implementation of education in schools in their capacities as advisers, program supporters, controllers, and even mediators. (3) The leadership of the school principal in improving the quality of education is very effective in managing the existing infrastructure and if something is incomplete, he immediately tries to complete it so that the learning process runs optimally. (4) The school work team carries out its duties as a school development team, namely by providing input to schools as material for consideration in making decisions, carrying out coaching to improve teacher abilities, making school development plans and preparing reports on the implementation of tasks.